Memaksimalkan Keuntungan Harian pada Industri Rumahan “Eka Jaya” dengan Penerapan Metode Simpleks - Pesta Gultom; Lucky Tiur A. Marbun; Adania Telaumbanua; Rasti Purba; Shilvia Maria A. Siagian (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The home industry "Eka Jaya" is a small business engaged in the production of snacks. In an effort to increase efficiency and daily profits, an optimal production planning method is needed. This study aims to maximize daily profits through the application of the simplex method in compiling the right production strategy. The simplex method is used to solve linear programming problems by maximizing the objective function in the form of profit and considering resource constraints such as raw materials, labor, and production time. The results of the study indicate that the application of the simplex method is able to provide an optimal production combination that produces maximum profit compared to the conventional method that has been used so far. Thus, this method can be used as a reference in making production decisions in the home industry "Eka Jaya".